An albedo electron method for measuring the density of P/M materials; Soviet Powder Metallurgy and Metal Ceramics; Vol. 20, iss. 8 - Kononov B. A. Boris Aleksandrovich; Rudenko V. N.; Sorokin V. B. Vladimir Borisovich; Vinogradov G. A.; Katrus O. A.; Sakhnenko A. V. (1981, 1981)
Title screen